Krüppel-like factors in breast cancer: Function, regulation and clinical relevance - Jianping Zhang (Biomedicine & Pharmacotherapy, 2020)
Breast cancer has accounted for the leading cause of cancer-related mortality among women worldwide. Although the progress in its diagnosis and treatment has come at a remarkable pace during the past several decades, there are still a wide array of problems regarding its progression, metastasis and treatment resistance that have not yet been fully clarified. Recently, an increasing number of studies have revealed that some members of Krüppel-like factors(KLFs) are significantly associated with cell proliferation, apoptosis, metastasis, cancer stem cell regulation and prognostic and predictive value for patients in breast cancer, indicating their promising prognostic and predictive potential for breast cancer survival and outcome. In this review, we will summarize our current knowledge of the functions, regulations and clinical relevance of KLFs in breast cancer.